1995
DOI: 10.1111/j.1600-0773.1995.tb00164.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long‐Term Antiepileptic Therapy on the Catabolism of Testosterone

Abstract: The serum levels of testosterone, sex hormone binding globulin, and free testosterone index were measured in 51 epileptic men (age 18-45) in order to assess the possible effects of antiepileptic drugs on sexual dysfunction. An analytical gas chromatography-mass spectrometry method was developed to assess the urinary excretion of testosterone, epitestosterone, androsterone, etiocholanolone, 11-OH androsterone and 11-OH etiocholanolone and to evaluate if the catabolism of testosterone had been increased. Twenty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Similarly, the data in the literature indicates that VPA therapy appears to have no effect on SHBG levels [38,42,44,46,47,51]. Concerning CBZ therapy, in a number of studies CBZ enhanced serum SHBG [34,44,46,48,49,51,57,62] but the effect on serum SHBG was reversible [51]. On the other hand, there are several studies in which the effect of CBZ on SHBG did not reach significance [42,43].…”
Section: Testosterone 5˛-dihydrotestosterone 5˛/ˇ-androstane-3˛/ˇ-dmentioning
confidence: 83%
See 2 more Smart Citations
“…Similarly, the data in the literature indicates that VPA therapy appears to have no effect on SHBG levels [38,42,44,46,47,51]. Concerning CBZ therapy, in a number of studies CBZ enhanced serum SHBG [34,44,46,48,49,51,57,62] but the effect on serum SHBG was reversible [51]. On the other hand, there are several studies in which the effect of CBZ on SHBG did not reach significance [42,43].…”
Section: Testosterone 5˛-dihydrotestosterone 5˛/ˇ-androstane-3˛/ˇ-dmentioning
confidence: 83%
“…Brunet et al evaluated the effects of long-term antiepileptic therapy on the catabolism of testosterone and followed urinary excretion of androsterone, etiocholanolone and their 11␤-hydroxy-metabolites [34]. However, although anticonvulsant properties were demonstrated for unconjugated androsterone and etiocholanolone [21], there are no studies available evaluating serum free or conjugated 3␣/␤-hydroxy-5␣/␤-androstane-17-ones in MWE.…”
Section: C19 5˛/ˇ-reduced-17-oxo-metabolitesmentioning
confidence: 97%
See 1 more Smart Citation
“…As these testosterone metabolites are produced via further reduction by 17â-hydroxysteroid dehydrogenase (after sequential actions by 5á-reductase and 3á-hydroxysteroid dehydrogenase), one can surmise that finasteride would decrease levels of androsterone and etiocholanolone. Notably, androsterone and etiocholanolone are the major excreted metabolites of testosterone (15,126), and long term antiepileptic drug therapy was found to decrease urinary excretion of both metabolites (e.g., 15). Thus, it was suggested that a reduction in GABAergic testosterone metabolites in men with epilepsy could contribute to increased seizure susceptibility (76).…”
Section: Animal Models Of Epileptic and Absence Seizuresmentioning
confidence: 99%
“…Reference intervals may lack statistical power and can be biased due to: 1) unintentional inclusion of hypogonadal subjects, which can be limited by testicular examination and a medical history focusing on testicular, pituitary, and chronic diseases (14), medication (15)(16)(17)(18)(19), excessive alcohol intake (20), and anabolic steroid abuse; 2) failure to recruit a population-based sample not mirroring the general population; 3) inappropriate timing of blood sampling; and 4) use of inaccurate testosterone assays. Commercially available direct immunoassays for assessment of total testosterone are widely used, but these assays suffer from a lack of accuracy (21)(22)(23)(24).…”
mentioning
confidence: 99%